CO2 Reduction: Continuous 3D Titanium Nitride Nanoshell Structure for Solar‐Driven Unbiased Biocatalytic CO2 Reduction (Adv. Energy Mater. 25/2019). Issue 25 (5th July 2019) - Kuk, Su Keun; Ham, Youngjin; Gopinath, Krishnasamy; Boonmongkolras, Passarut; Lee, Youngjun; Lee, Yang Woo; Kondaveeti, Sanath; Ahn, Changui; Shin, Byungha; Lee, Jung‐Kul; Jeon, Seokwoo; Park, Chan Beum
Abstract : In article number1900029, Jung‐Kul Lee, Seokwoo Jeon, Chan Beum Park and co‐workers report a titanium nitride nanoshell structure as a cathode material for biocatalytic photoelectrochemical cells, which can reduce carbon dioxide to formic acid through light‐driven, direct electron transfer. The leaf‐like platform mimics the Z‐scheme of natural photosynthesis for sustainable carbon dioxide reduction using solar energy and water.